Impact of silver ions and silver nanoparticles on the plant growth and soil microorganisms - D. Tomacheski; M. Pittol; D.N. Simões; V.F. Ribeiro; R.M.C. Santana (Global Journal of Environmental Science and Management)
There is a growing consumer market for products that proclaim to decrease microorganism counts to prevent infections. Most of these products are loaded with silver in its ionic or nanoparticle form. Through use or during production, these particles can find their way into the soil and cause an impact in microbial and plant communities. This study aims to evaluate the impact of silver based particles in Avena byzantina (oat), Lactuca sativa (lettuce) and Raphanus sativus (radish) development and in the soil microorganism abundance. Oat, lettuce and radish plants were cultivated in soil contaminated with particles of bentonite organomodified with silver (Ag+_bentonite), silver phosphate glass (Ag+_phosphate) and silver nanoparticles adsorbed on fumed silica (AgNp_silica). Plant development and microorganisms’ abundance were evaluated. To some degree, Ag+_bentonite impacted plants development and AgNp_silica causes an adverse effect on microbial abundance. The impact on plants and microorganisms was contradictory and varied according to soil and particles physicochemical characteristics.